Opportunities and Constraints with Ethnography in Examining the Home Literacy Experiences of English Language Learners - Shi, Zihan (Alberta Journal of Educational Research, 2012)
This paper is intended for researchers considering using ethnography as a methodology to investigate home literacy experiences of children learning English as a Second Language (ESL). After briefly setting ethnographic study in the context of English language learners’ home literacy practices, I identify five opportunities and five potential constraints using examples from current literature in the research field. The five opportunities include (a) examination of a cultural group, (b) extensive time in the field, (c) multiple sources of data collection, (d) context or setting of the study, and (e) researcher reflexivity. The five constraints include (a) identification of a culture-sharing group, (b) extensive time in the field, (c) prior relationships with participants, (d) communication with immigrant families, and (e) translation issues. I present these so that researchers can understand more readily the opportunities and challenges they may face in exploring the home literacy experiences of immigrant children through ethnography. Cet article vise les chercheurs qui considèrent employer une approche ethnographique pour étudier les expériences en littératie que vivent, chez eux, des enfants qui apprennent l'anglais comme langue seconde. Après avoir rapidement placé l'étude ethnographique dans le contexte des pratiques littéraires qu'emploient les apprenants d'anglais chez eux, j'identifie, par le biais d'exemples de la littérature actuelle du domaine de recherche, cinq possibilités et cinq contraintes potentielles. Les cinq possibilités sont les suivantes: (a) l'étude d'un groupe culturel, (b) la grande période de temps sur le terrain, (c) plusieurs sources de cueillette de données, (d) le contexte ou milieu de l'étude et (e) la réflexivité du chercheur. Les cinq contraintes sont les suivantes: (a) l'identification d'un groupe qui partage une culture, (b) les rapports préalables avec les participants, (d) la communication avec les familles immigrantes et (e) les enjeux liés à la traduction. Je présente ces dix éléments de sorte à ce que les chercheurs comprennent mieux les possibilités et les défis qui pourraient accompagner les études ethnographiques portant sur les expériences en littératie que vivent les enfants immigrants à la maison.